Estudo de sensibilidade do modelo Brams às variações dos parâmetros de superfície do Nordeste do Brasil - Costa, Roner Ferreira da (2007)
In this work a numeric experiment was accomplished with the model BRAMS (Brazilian Regional Atmospheric Modeling System) with the purpose of studying the changes in the surface variables due to the variations of the surface parameters as soil moisture and the vegetation class in the Northeast of Brazil which are input in BRAMS. They were made three simulations, the first (simulation control) it was initialized with the standard files of the own model, the second simulation was maintained the class of vegetation pattern (Deciduous shrub) and just altering the soil moisture and the third simulation alters the vegetation for semi-desert besides reducing the humidity of the soil. Also a validation of the model was accomplished with a soil humidity made calculations starting from observed data of precipitation. It is verified that the humidity of the soil and the vegetation have a strong influences on the climate of the Northeast area of Brazil; however it is not very significant in the weather forecast.